A Mode-Matching-Based Technique for Electromagnetic Characterization of Anisotropic Materials in Cylindrical Waveguides - Rodrigues, Ricardo R.; Cosenza, Vivian B.; Rosa, Guilherme S.; Penchel, Rafael A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this paper, we present a mode-matching technique (MMT) formulation for the electromagnetic characterization of measurement cells (MCs) for uniaxial anisotropic materials. We present and validate a technique for modeling MCs with one- and two-ports via generalized scattering matrices (GSMs) extracted from the MMT. Since closed-form solutions are used for computing the coupling integrals of the GSMs, the present approach is a computationally-efficient alternative to modeling MCs when compared to usual brutal-force techniques. An inverse algorithm is also presented to retrieve the constitutive parameters of complex media (lossy and anisotropic materials). Differently from the majority of the works using semi-analytical methods, the novelty of the present method rely on considering overmoded MCs.
Keywords: anisotropic media; measurement cell; mode-matching technique